Coating method for improving adhesion strength of metal coating on surface of high polymer material and composite film

By using metal vapor vacuum arc ion implantation technology to inject metal ions on the surface of polymer materials, combined with magnetic filter cathode arc deposition technology, a metal composite film with high adhesion strength is formed, which solves the problem of low adhesion strength of metal coatings on the surface of polymer materials. Significantly improves the performance and safety of lithium batteries.

CN119332218APending Publication Date: 2025-01-21CHONGHUI SEMICON (JIANGMEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411382238.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The metal coating on the surface of polymer materials has low adhesion strength, which causes the coating to fall off easily, affecting the safety and performance of the battery.

Method used

Metal vapor vacuum arc ion implantation technology is used to inject metal ions on the surface of polymer materials, and the thickness of the metal film is increased through magnetic filter cathode arc deposition to form a metal composite film with high adhesion strength.

Benefits of technology

It significantly improves the adhesion strength of the metal coating on the surface of the polymer material, improves the electrochemical performance and safety performance of the lithium battery, and avoids the risk of coating peeling and battery short circuit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332218A_ABST
    Figure CN119332218A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of inorganic metal film materials, in particular to a coating method for improving adhesion strength of a metal coating on the surface of a high polymer material and a composite film, and the coating method comprises the following steps: S1, performing metal steam vacuum arc ion implantation on the surface of the high polymer material to obtain a metal film on the surface of the high polymer material, the structure of the composite high polymer material is that a part of the metal material is embedded into the high polymer material, and a part of the metal material remains on the surface; wherein the injection dose of the metal steam vacuum arc ion injection is 2.5 * 10 < 17 >-4.0 * 10 < 17 > cm <-2 >; and S2, metal deposition is conducted on the surface of the composite high polymer material in the step S1 through a magnetic filtering cathode arc deposition method, the deposited metal material is the same as the injected metal material, and the high polymer material surface metal composite film is obtained. By means of the film coating method, the high polymer material surface metal composite film which is good in adhesion and adjustable in thickness can be obtained, and the metal composite film is high in adhesion strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparation of inorganic metal film materials, and in particular to a coating method for improving the adhesion strength of metal coatings on the surface of polymer materials. Background Art

[0002] The current collector is an important functional component of the positive and negative electrodes of the battery. The traditional current collector uses relatively pure aluminum foil or copper foil, while the composite current collector is a battery material with a "sandwich" structure. The outer two layers are copper metal or aluminum metal, and the main middle layer is a polymer material such as polyethylene terephthalate (PET), polypropylene (PP) or polyimide (PI). The mainstream process of new energy lithium-ion batteries is aluminum foil for the positive electrode collector and copper foil for the negative electrode collector. The good conductor material with a thickness of about 1 micron is "pasted" on both sides of the base film material by vacuum deposition, electroplating, etc., which not only has the advantage of lightweight, but also produces almost no metal burrs when the battery is broken by external impact, avoiding puncturing the battery diaphragm and reducing the risk of battery short circuit. Even if the battery is short-circuited due to puncture and other reasons, the composite current collector is more likely to be melted when a short circuit occurs. Therefore, when the battery is damaged, it will melt quickly to block the current, avoiding the risk of battery combustion and explosion, and effectively improving safety. In addition, the composite current collector can also increase the service life of the battery. It has significant advantages in many application scenarios such as new energy vehicles, energy storage and consumer battery applications, and is expected to quickly become a new generation of key battery materials that improve battery safety, energy density and reduce battery costs. It can be applied to power, energy storage and other fields, bringing new technical directions to the development of the new energy battery industry and helping to promote the further upgrading of my country's new energy battery industry technology.

[0003] With the continuous advancement of technology and the increasing market demand for lightweight and high-performance materials, composite current collectors are expected to have broad application prospects in the field of new energy. In terms of the preparation technology of current collectors, it usually includes chemical plating, one-step all-wet process, "magnetron sputtering + water electroplating" two-step method and all-dry method. For example, the two-step method of vacuum magnetron sputtering + post-water electroplating is used. The vacuum coating equipment of some companies can complete the coating in one chamber, without water electroplating, and without switching between dry and wet methods. It is environmentally friendly and can also improve the yield rate, such as magnetron sputtering + evaporation coating all-in-one machine. In the preparation process, core technologies such as surface interface modification and deposition layer regulation are included. For example, when improving the adhesion of the coating, the surface roughening liquid can be used to treat the substrate. At present, polymer materials as substrates have problems such as low adhesion strength and easy falling off. The coating methods and technologies still need to be improved, but the improvement method of related technologies is to improve the bonding strength and stability of the coating by modifying the process parameters.

[0004] In order to fully utilize the advantages of various materials and realize the industrial application of composite current collectors, such as in the fields of high-end power batteries, it is urgent to develop a simple and reliable preparation method to obtain high-quality composite current collector materials. Summary of the invention

[0005] The purpose of the present application is to overcome the defect of low adhesion strength of metal coatings on the surface of polymer materials. The present application provides a coating method for improving the adhesion strength of metal coatings on the surface of polymer materials.

[0006] In the first aspect, the present application provides a coating method for improving the adhesion strength of metal coating on the surface of polymer materials, which adopts the following technical solution: A coating method for improving the adhesion strength of a metal coating on a polymer material surface comprises the following steps: S1. Metal ion implantation is performed on the surface of the polymer material by metal vapor vacuum arc ion implantation technology to obtain a metal film on the surface of the polymer material, wherein part of the metal material of the metal film on the surface of the polymer material is embedded in the polymer material, and part of the metal material remains on the surface; The implantation dose of the metal vapor vacuum arc ion implantation is 2.5×10 17 ~4.0×10 17 cm -2 ; S2. On the metal film on the surface of the polymer material in step S1, a magnetic filtration cathode arc deposition method is used to deposit metal, and the deposited metal material is the same as the injected metal material to obtain a metal composite film on the surface of the polymer material.

[0007] This application applies MEVVA ion implantation technology (metal vapor vacuum arc ion implantation technology) to the surface modification of polymer materials and the deposition of metal thin films, mainly for the preparation of electrode materials in composite current collectors. In the process of ion implantation, on the one hand, the surface composition of the polymer material changes due to the injection of metal ions, and the implantation material and the matrix material are included within the range of the implantation depth. In addition, since the implantation depth is not a fixed value, but there is a certain depth distribution, by controlling the appropriate implantation dose, some metal atoms can remain on the surface of the material to form a nanofilm, while some of the implanted atoms are combined with the substrate to form a structure in which the metal film is partially embedded in the substrate; the same metals have good bonding properties, so after the metal is injected into the substrate surface, when the same metal material as the metal injection is further deposited, the deposited film can be reliably bonded to the polymer substrate.

[0008] The present application firstly injects an appropriate amount of metal ions into the surface of the polymer material through the metal vapor vacuum arc ion implantation technology, and obtains a metal film with good adhesion between the metal and the polymer material by controlling the implantation dose and energy, and then uses magnetic filtration cathode arc deposition to increase the thickness of the metal film, thereby obtaining a metal composite film with good adhesion and adjustable thickness. The metal composite film on the surface of the polymer material has high adhesion strength. On the other hand, the metal plating method of the present application avoids the wet process, is environmentally friendly and reliable, and the obtained metal composite film has broad application prospects in new energy current collectors, especially in high-end consumer and power batteries.

[0009] Optionally, the polymer material is selected from one of polyethylene terephthalate, polypropylene and polyimide; and / or the polymer material is in the form of a sheet or a film.

[0010] By adopting the above technical solution, the present application can coat the surface of polymer materials such as PET, PP and PI, and obtain metal composite films on the surface of polymer materials with excellent performance, and these materials can also be modified by various surface treatment technologies to meet different application requirements. The polymer materials in sheet or film form can be easily cut into various shapes and sizes, with excellent processing performance and flexibility.

[0011] Optionally, in step S1, the metal ions inside the polymer material are a discontinuous structure, the metal ions on the surface of the polymer material are a continuous / discontinuous structure, and the metal ions in the internal area of ​​the polymer material and the metal material in the surface area form a continuous connection structure based on physical and / or chemical forces.

[0012] By adopting the above technical solution, the metal material of the injected part can form an effective connection with the surface part, thereby forming a "metal-polymer" interface layer. This interface layer has better adhesion and stability, can resist the influence of external environmental factors such as corrosion and wear, and improve the adhesion strength of the metal composite film.

[0013] Optionally, in step S1, the element implanted by metal vapor vacuum arc ion implantation is selected from one of copper, aluminum and cobalt.

[0014] By adopting the above technical solution, copper, aluminum and cobalt elements all have excellent conductive properties. By injecting them into polymer materials through ion implantation, the conductive properties of the polymer materials can be improved. In addition, copper, aluminum and cobalt elements have low atomic numbers and high kinetic energy, and can better penetrate the surface layer of the polymer material, combine with the polymer material, and improve the adhesion between the metal coating and the polymer material.

[0015] Optionally, in step S1, the parameters of metal vapor vacuum arc ion implantation are: The vacuum degree is 4×10 -4 ~6×10 -4 Pa, the ion generation frequency is 5 to 10 Hz, and the injection energy is 15 to 30 keV.

[0016] Optionally, in step S1, the parameters of the metal vapor vacuum arc ion implantation are specifically: The vacuum degree is 5×10 -4 Pa, the ion generation frequency is 10 Hz, and the injection energy is 20 keV.

[0017] By adopting the above technical solution and selecting the appropriate vacuum degree, the influence of impurities and gases on the ion implantation process can be avoided, and the ion implantation efficiency can be improved, thereby improving the quality of the coating. The ion generation frequency parameter determines the number of ions generated per unit time. Controlling the appropriate ion generation frequency can make the ion implantation process more stable and controllable. The injection energy parameter determines the depth and range of the ion injection. Controlling the appropriate injection energy can make the coating more uniform and improve the adhesion strength of the coating.

[0018] Optionally, in step S2, the parameters of the magnetic filtration cathode arc deposition are: The vacuum degree is 5×10 -4 ~8×10 -4 Pa, the accelerating voltage applied to the metal ions during the deposition of metal ions is 100 to 900 V.

[0019] Optionally, in step S2, the parameters of the magnetic filtration cathode arc deposition are specifically: The vacuum degree is 5×10 -4 Pa, and the accelerating voltage applied to the metal ions during the deposition of the metal ions is 300 V.

[0020] By adopting the above technical solution, an accelerating voltage is applied to the metal ions during the deposition of the metal ions, so that the metal ions can obtain sufficient energy, thereby being better deposited on the surface of the polymer material to form a uniform and dense metal film.

[0021] Optionally, in step S1, the thickness of the injection layer of the metal film on the surface of the polymer material is 60 to 150 nm.

[0022] Optionally, the thickness of the metal ion implantation layer is 100 nm, and the metal ion implantation layer includes about 70 nm embedded in the polymer material and 30 nm remaining on the surface of the polymer material.

[0023] By adopting the above technical solution and controlling the parameters of metal vapor vacuum arc ion implantation, a suitable implantation layer thickness can be obtained and the adhesion strength of the metal film can be improved.

[0024] Optionally, the thickness of the metal film prepared by the magnetic filtration cathode arc deposition is adjusted in the range of 10 nm to 5 μm to meet the current collector's requirement for the thickness of the metal composite film.

[0025] By adopting the above technical solution, the thickness of the metal film will directly affect its conductive properties. Within a certain range, a thicker metal film has a lower resistivity and a higher conductivity. Therefore, according to the requirements of the current collector, a metal composite film with different properties can be obtained by adjusting the thickness of the metal film to meet the requirements of different current collectors.

[0026] Optionally, the polymer material is pretreated before metal ion implantation, and the pretreatment includes the following steps: The polymer material is cut and then cleaned with a cleaning agent; the cleaning agent is selected from at least one of acetone, ethanol and deionized water.

[0027] By adopting the above technical solution, pretreatment can remove stains on the surface of the polymer material, keep the surface of the polymer material clean, facilitate metal coating, and improve the adhesion strength of the metal coating.

[0028] In the second aspect, the present application provides a metal composite film adopting the following technical solution: A metal composite film on the surface of a polymer material is obtained by adopting the metal coating method of the present application.

[0029] By adopting the above technical solution, compared with the traditional coating method, the coating method of the present application can improve the adhesion strength of the metal coating on the surface of the polymer material, thereby improving the electrochemical performance and safety performance of the lithium battery.

[0030] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application firstly injects an appropriate amount of metal ions into the surface of the polymer material by metal vapor vacuum arc ion implantation technology, and obtains a metal film with good adhesion between the metal and the polymer material by controlling the implantation dose and energy, and then uses magnetic filtration cathode arc deposition to increase the thickness of the metal film, so as to obtain a metal composite film with good adhesion and adjustable thickness. The metal composite film on the surface of the polymer material has high adhesion strength; on the other hand, the metal coating method of the present application avoids the wet process, is environmentally friendly and reliable, and the obtained metal composite film has broad application prospects in new energy current collectors, especially high-end consumer and power batteries; 2. The metal vapor vacuum arc ion implantation technology used can be used as an ion source for conductive solids, and common elements such as copper, aluminum and cobalt can be used as ion sources. Compared with the traditional implantation technology, the beam current is larger, the injection speed is faster, and the time consumption is shorter. Usually, a single dose of injection can be completed within 1 hour, while the traditional implantation technology takes several hours to more than ten hours; since the large injection beam current makes it easy to obtain high-dose injection, it is crucial for the formation of a thin film on the surface layer of the polymer material; 3. Using magnetic filtration cathode arc deposition, metal films with a thickness of microns can be quickly prepared within a few minutes. At the same time, the flow and energy of the deposited ion beam can be controlled to achieve efficient and high-quality preparation of polymer-surface metal composite films. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the coating method process of the present application; Figure 2 is a cross-sectional SEM image of the metal composite film of Example 1; Figure 3 is a cross-sectional SEM image of the metal composite film of Example 2; Figure 4 This is a cross-sectional SEM image of the metal composite film of Comparative Example 1. DETAILED DESCRIPTION

[0032] The content of this application is further described in detail below through specific examples.

[0033] Unless otherwise specified, the injection volume in this application is in cm -2 ” is “ions·cm -2 "; The metal vapor vacuum arc (MEVVA) ion implantation system and the magnetic filtered arc ion deposition system used in this application are integrated into the same vacuum system.

[0034] The PP matrix is ​​a homopolymer polypropylene matrix.

[0035] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0036] The present application provides a coating method for improving the adhesion strength of metal coating on the surface of polymer materials, referring to Figure 1 , using polymer materials as the matrix, the metal vapor vacuum arc ion implantation technology is used to first prepare a nanometer-scale metal film with good adhesion on the surface of the polymer matrix, with a thickness of 60 to 150 nm. Then, in the same vacuum system, the magnetic arc source deposition technology is used to continue to deposit the same element. The thickness of the metal film prepared by magnetic filtered cathode arc deposition is adjusted from 10 nm to 5 μm. In a preferred example, the thickness of the metal composite film reaches 1 to 2 μm to meet the general requirements of the current collector. Example

[0037] Example 1 The method for preparing a metal composite film on a polymer material surface provided in this embodiment comprises the following steps: S1. Pretreatment: Cut the PP substrate into several pieces of 10cm×10cm (length×width, i.e., the orthographic projection area is 100cm 2 ) was cleaned with acetone, ethanol and deionized water in sequence; S2. Metal vapor vacuum arc ion implantation: Place the pretreated PP substrates into the implantation chamber, and place one side of the PP substrate facing the cobalt ion source to implant metal ions on the surface of the PP substrate. Set the parameters as follows: The ion generation frequency is 10 Hz, and the vacuum degree in the injection chamber is 5×10 -4 Pa, the injection energy was set to 20 kV, and the ion beam generation frequency was 10 Hz; The injection volume was set to 3.0 × 10 17 cm -2 , a metal film is obtained on the surface of the PP substrate; S3. Magnetic filtration cathode arc ion deposition: After the injection is completed, the sample stage is rotated to the direction of magnetic filtration cathode arc deposition. The magnetic filtration cathode arc ion deposition method is used to increase the thickness of the metal film on the surface of the PP substrate. The acceleration voltage applied to the ions is 300V, the cumulative charge of the sample stage is 6000×50mC, and the deposition time is 5min to obtain a metal electroplated film on the surface of the PP material.

[0038] Example 2 The method for preparing a metal composite film on a polymer material surface provided in this embodiment comprises the following steps: S1. Pretreatment: Cut the PP substrate into several pieces of 10cm×10cm (length×width, i.e., the orthographic projection area is 100cm 2 ) was cleaned with acetone, ethanol and deionized water in sequence; S2. Metal vapor vacuum arc ion implantation: Place the pretreated PP substrates into the implantation chamber, and place one side of the PP substrate facing the copper ion source to implant metal ions on the surface of the PP substrate. Set the parameters as follows: The ion generation frequency is 10 Hz, and the vacuum degree in the injection chamber is 5×10 -4 Pa, the injection energy was set to 20 kV, and the ion beam generation frequency was 10 Hz; The injection volume was set to 3.0 × 10 17 cm -2 , a metal film is obtained on the surface of the PP substrate; S3. Magnetic filtration cathode arc ion deposition: After the injection is completed, the sample stage is rotated to the direction of magnetic filtration cathode arc deposition. The magnetic filtration cathode arc ion deposition method is used to increase the thickness of the metal film on the surface of the PP substrate. The acceleration voltage applied to the ions is 300V, the cumulative charge of the sample stage is 22000×50mC, and the deposition time is 15min to obtain a metal electroplated film on the surface of the PP material.

[0039] Example 3 The difference between this embodiment and embodiment 2 is that the PP matrix is ​​replaced by a PET matrix, and the remaining components and steps are the same as those in embodiment 2.

[0040] Example 4 The difference between this embodiment and embodiment 2 is that the PP matrix is ​​replaced by a PI matrix, and the remaining components and steps are the same as those in embodiment 2.

[0041] Example 5 The difference between this embodiment and embodiment 2 is that the copper ion source is replaced by an aluminum ion source, and the remaining components and steps are the same as those in embodiment 2.

[0042] Example 6 The difference between this embodiment and embodiment 2 is that the injection amount is set to 2.5×10 17 cm -2. , the remaining components and steps are the same as those in Example 2.

[0043] Example 7 The difference between this embodiment and embodiment 2 is that the injection amount is set to 3.5×10 17 cm -2. , the remaining components and steps are the same as those in Example 2.

[0044] Example 8 The difference between this embodiment and embodiment 2 is that the injection amount is set to 4.0×10 17 cm -2. , the remaining components and steps are the same as those in Example 2.

[0045] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that the metal vapor vacuum arc ion implantation step is not performed, and the remaining components and steps are the same as those in Example 1.

[0046] Comparative Example 2 The difference between this comparative example and Example 2 is that the metal vapor vacuum arc ion implantation step is not performed, and the remaining components and steps are the same as those in Example 2.

[0047] Comparative Example 3 The difference between this comparative example and Example 2 is that, during the magnetic filtration cathode arc ion deposition, the copper ion source is replaced by a cobalt ion source, and the remaining components and steps are the same as those in Example 2.

[0048] Comparative Example 4 This comparative example uses aluminum foil as the metal composite film on the surface of the polymer material.

[0049] Performance Testing The metal composite films on the surfaces of the polymer materials provided in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to the following performance tests.

[0050] 1. SEM Characterization The cross-section of the metal composite film on the surface of the polymer material provided in Examples 1 to 2 and Comparative Example 1 was characterized by SEM. The characterization results are shown in Figures 2-3 .

[0051] Depend on Figure 2 It can be seen that in Example 1, the thickness of the prepared metal composite film is about 400nm, and the connection with the substrate is good; Figure 4 It can be seen that in Example 2, the thickness of the prepared metal composite film is about 1450nm, and the connection with the substrate is also good. It also further illustrates that by adjusting the deposition time of the magnetic filtration cathode arc ion deposition, the thickness of the metal composite film can be adjusted to meet the current collector's requirements for the thickness of the metal composite film.

[0052] In addition, by Figure 4 It can be seen that in Comparative Example 1, the metal vapor vacuum arc ion implantation step was not used, and copper was directly plated on the surface of the PP material, which easily caused the film to separate from the substrate. It also further illustrates that if the traditional coating method is used, when the thickness of the coating is low, the adhesion between the coating and the substrate is very poor, and the stability of the obtained current collector is poor, which affects the performance of the battery; while the coating method of the present application can significantly improve the adhesion strength of the coating, obtain a metal composite film with excellent performance, and has broad application prospects.

[0053] 1. Peel strength test According to GB / T 1457-2005, three parallel samples were cut from the metal composite film on the surface of the polymer material. The samples were in strip shape with the dimensions of 15 mm in width and 100 mm in length. Then, a stainless steel plate with a surface roughness of 50±25 nm was wiped with an alcohol dust-free cloth. The conductive layer of the sample to be tested was then fixed on the stainless steel plate with double-sided tape. After rolling back and forth twice with a 2kg manual pressure wheel, the stainless steel plate with the sample to be tested was installed on the machine fixture. A multifunctional tensile machine was used for 180° peeling. The tensile speed of the multifunctional tensile machine was set to 100 mm / min. The peeling test was started until the metal composite film to be tested was completely peeled off from the polymer material, and the test was stopped and the peeling force value was read.

[0054] 2. Battery electrochemical performance The metal composite film on the surface of the polymer material provided in Examples 1 to 8 and Comparative Examples 1 to 4 was prepared by a conventional method to prepare a lithium cobalt oxide positive electrode sheet and a graphite negative electrode sheet, and assembled into a button battery with a PP2400 separator, a lithium sheet, and a conventional lithium ion electrolyte. The test was carried out using a Xinwei battery test system, with a voltage range of 3.0 to 4.3V, a charge and discharge rate of 0.2C, and the first efficiency was tested.

[0055] Mass energy density: Charge each lithium-ion battery at a rate of 0.2C to the full charge voltage of 4.45V, charge at a constant voltage to a cut-off current of 0.025C, and leave for 10 minutes; discharge at a rate of 0.2C to a rated lower limit voltage of 3.0V, record the capacity and energy of the battery, and weigh the battery using a balance. The mass energy density of the battery is equal to the ratio of the battery energy to the battery mass.

[0056] Cycle performance: At room temperature, charge with constant current and constant voltage, limit current of 1.1C, and end voltage of 4.2V; discharge with constant current, discharge current of 1.0C, and end voltage of 3.0V. Cycle 400 times, and calculate the capacity retention rate after 400 cycles.

[0057] 4. Battery safety performance Battery nail penetration test: After the battery is fully charged in the standard charging mode, perform a nail penetration test within 24 hours. First, place the battery on a plane, and use a steel nail with a diameter of 3mm to vertically pierce the battery at a speed of 150mm / s. After the steel nail pierces the battery, it continues to remain in the battery for 5 minutes or the battery surface temperature drops to 50℃, then stop the test. If the battery does not catch fire or explode, it means that the battery has passed the test. Test 10 parallel samples, and the ratio of the number of samples that pass the test to the total number of test samples is taken as the pass rate of the nail penetration test.

[0058] Battery hot box test: After fully charging the battery in the standard charging mode, perform a hot box test within 24 hours. Place the battery in a hot box and raise the temperature to 90°C at 5°C / min, then keep the temperature constant for 30 minutes to observe whether the battery burns or explodes. If the battery does not burn or explode, take another battery and repeat the process, keeping the temperature raised by 3°C until the battery burns or explodes.

[0059] The test results are shown in Table 1.

[0060] Table 1: Test results of Examples 1 to 8 and Comparative Examples 1 to 4 Referring to Table 1, combined with the test results of Example 1 and Comparative Example 1, it can be seen that after metal vapor vacuum arc ion implantation treatment, the peel strength of the metal composite film on the surface of the polymer material is significantly improved, which shows that by metal vapor vacuum arc ion implantation technology, metal ions are implanted on the surface of the polymer material to obtain a structure in which part of the metal material is embedded inside and part of the metal material is retained on the surface. This structure can significantly improve the adhesion strength between the coating and the polymer material. At the same time, it can also be seen that when the metal composite film provided in Example 1 is applied to a lithium battery, its electrochemical performance and safety performance are improved. This is because the metal electroplating film with strong adhesion can better fix the electrode active material and prevent it from falling off or deforming during the charging and discharging process, which is conducive to maintaining the stability of the electrode structure, thereby improving the mass energy density and cycle life of the lithium battery, and also improving the safety of the battery; secondly, it can also improve the conduction efficiency of electrons in the current collector, reduce the internal resistance of the battery, and thus improve the charging and discharging efficiency of the lithium battery. Improved adhesion also helps to improve the thermal stability of the current collector, so that it can maintain the stability of the structure and performance under higher temperature environments.

[0061] Combining the test results of Example 2 and Comparative Example 2, it can be seen that Example 2 is better than Comparative Example 2, which further illustrates that the metal vapor vacuum arc ion implantation technology can improve the adhesion strength between the coating and the polymer material and improve the performance of the lithium-ion battery.

[0062] Combined with the test results of Examples 2 to 4, it can be seen that the coating method of the present application can be used for coating on the surface of polymer materials such as PET, PP and PI to obtain a metal composite film on the surface of the polymer material with excellent performance, and the performance of the lithium-ion battery produced is also relatively good.

[0063] Combining the test results of Example 2 and Comparative Example 3, it can be seen that Example 2 is better than Comparative Example 2, which shows that the bonding between the same metals is better. Therefore, after the metal is injected into the surface of the substrate, when the same metal material as the metal injection is further deposited, a reliable bonding between the deposited film and the polymer substrate can be achieved.

[0064] Combining the test results of Examples 2, 6 to 8, it can be seen that different injection amounts affect the performance of the metal electroplating film on the surface of the polymer material and the lithium battery. 17 cm -2 When the adhesion strength of the metal composite film on the surface of the polymer material is optimal, the obtained lithium battery performance is also optimal.

[0065] In Examples 2 to 5, the same working parameters of metal vapor vacuum arc ion implantation and magnetic filtration cathode arc ion deposition are used, but the difference is that different metal ion sources or substrates are used, but the performance of the obtained metal composite film and lithium battery is better; it shows that the coating process of the present application has a wide range of applications, can significantly improve the adhesion strength of the metal coating, and improve the performance of lithium batteries, especially in terms of safety performance. In addition, combined with the test results of Comparative Example 4, it can be seen that although the traditional aluminum foil is close to the embodiment of the present application in terms of electrochemical performance, its safety performance is relatively poor.

[0066] It can be seen that in the embodiments of the present application, the best embodiment is embodiment 2, and the parameters of the metal vapor vacuum arc ion implantation are as follows: the implantation amount is 3.0×10 17 cm -2 , vacuum degree is 5×10 -4 Pa, the ion generation frequency is 10Hz, the injection energy is fixed at 20keV, and the target material of the ion source is copper material; the parameters of magnetic filtration cathode arc ion deposition are as follows: the acceleration voltage applied to the ions is 300V, the cumulative charge of the sample stage is 22000×50mC, and the deposition time is 15min. The thickness of the injection layer of the obtained polymer metal composite film is about 100nm, including about 70nm embedded in the substrate, 30nm retained on the surface of the substrate, and the overall thickness of the metal composite film is about 1450nm.

[0067] In summary, the present application combines metal vapor vacuum arc ion implantation technology and magnetic filtration cathode arc deposition technology, and uses metal cobalt, aluminum or copper materials with good conductivity to prepare a composite film with good adhesion to polymer materials. The preparation method of the composite film is a one-step preparation method with simple operation and high reliability, and can be widely used in the production of composite current collector materials for new energy batteries.

[0068] The above is only a preferred embodiment of the present application and does not constitute any form of limitation to the present application. Therefore, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A coating method for improving the adhesion strength of metal coating on the surface of polymer materials, characterized in that: The following steps are involved: S1. Metal ion implantation is performed on the surface of the polymer material by metal vapor vacuum arc ion implantation technology to obtain a metal film on the surface of the polymer material, wherein part of the metal material of the metal film on the surface of the polymer material is embedded in the polymer material, and part of the metal material remains on the surface; The implantation dose of the metal vapor vacuum arc ion implantation is 2.5×10 17 ~4.0×10 17 cm -2 ; S2. On the metal film on the surface of the polymer material in step S1, a magnetic filtration cathode arc deposition method is used to deposit metal, and the deposited metal material is the same as the injected metal material to obtain a metal composite film on the surface of the polymer material.

2. According to claim 1, the coating method for improving the adhesion strength of metal coating on the surface of polymer materials, the polymer material is selected from one of polyethylene terephthalate, polypropylene and polyimide; the polymer material is in the form of sheet or film.

3. The coating method for improving the adhesion strength of metal coating on the surface of polymer materials according to claim 1, characterized in that: In step S1, the metal ions inside the polymer material are a discontinuous structure, the metal ions on the surface of the polymer material are a continuous / discontinuous structure, and the metal ions in the internal area of ​​the polymer material and the metal material in the surface area form a continuous connection structure based on physical and / or chemical forces.

4. The coating method for improving the adhesion strength of metal coating on the surface of polymer materials according to claim 1, characterized in that: In the step S1, the element implanted by the metal vapor vacuum arc ion implantation is selected from one of copper, aluminum and cobalt.

5. The coating method for improving the adhesion strength of metal coating on the surface of polymer materials according to claim 3, characterized in that: In step S1, the parameters of metal vapor vacuum arc ion implantation are: The vacuum degree is 4×10 -4 ~6×10 -4 Pa, the ion generation frequency is 5 to 10 Hz, and the injection energy is 15 to 30 keV.

6. The coating method for improving the adhesion strength of metal coating on the surface of polymer materials according to claim 3, characterized in that: In step S2, the parameters of the magnetic filtration cathode arc deposition are: The vacuum degree is 5×10 -4 ~8×10 -4 Pa, the accelerating voltage applied to the metal ions during the deposition of metal ions is 100 to 900 V.

7. The coating method for improving the adhesion strength of metal coating on the surface of polymer materials according to claim 5, characterized in that: In the step S1, the thickness of the injection layer of the metal film on the surface of the polymer material is 60-150 nm.

8. The coating method for improving the adhesion strength of metal coating on the surface of polymer materials according to claim 6, characterized in that: The thickness of the metal film prepared by the magnetic filtration cathode arc deposition is adjusted in the range of 10 nm to 5 μm to meet the requirements of the current collector for the thickness of the metal composite film.

9. The coating method for improving the adhesion strength of metal coating on the surface of polymer materials according to claim 1, characterized in that: The polymer material is pretreated before metal ion implantation, and the pretreatment includes the following steps: The polymer material is cut and then cleaned with a cleaning agent; the cleaning agent is selected from at least one of acetone, ethanol and deionized water.

10. A metal composite film on the surface of a polymer material, characterized in that: The metal coating method is obtained by any one of claims 1 to 9.